2023
DOI: 10.1038/s41467-023-39304-9
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the electron charge density in monolayer MoS2 at the Ångstrom scale

Abstract: Four-dimensional scanning transmission electron microscopy (4D-STEM) has recently gained widespread attention for its ability to image atomic electric fields with sub-Ångstrom spatial resolution. These electric field maps represent the integrated effect of the nucleus, core electrons and valence electrons, and separating their contributions is non-trivial. In this paper, we utilized simultaneously acquired 4D-STEM center of mass (CoM) images and annular dark field (ADF) images to determine the projected electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…In principle, the stability of the integrated charges under probe effects may also be affected by the probe shape which is defined by high-order aberrations. Indeed, recent investigations have demonstrated that in TMD monolayers the 4D-STEM estimated charge density at atomic sites can be influenced by second-order 3-fold astigmatism C 2,3 , and this effect depends upon the azimuthal angle of the aberration. , Notably, an apparent charge inversion between different atomic species can be observed under specific orientations of the probe aberrations. To investigate this effect, we convolved the DFT charge density considering a probe function with a size of 1.15 Å, consistent with our experimental estimations, and a 3-fold astigmatism of 30 nm, corresponding to the tolerance for the spherical aberration corrector of the STEM microscope employed (see Section V in the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In principle, the stability of the integrated charges under probe effects may also be affected by the probe shape which is defined by high-order aberrations. Indeed, recent investigations have demonstrated that in TMD monolayers the 4D-STEM estimated charge density at atomic sites can be influenced by second-order 3-fold astigmatism C 2,3 , and this effect depends upon the azimuthal angle of the aberration. , Notably, an apparent charge inversion between different atomic species can be observed under specific orientations of the probe aberrations. To investigate this effect, we convolved the DFT charge density considering a probe function with a size of 1.15 Å, consistent with our experimental estimations, and a 3-fold astigmatism of 30 nm, corresponding to the tolerance for the spherical aberration corrector of the STEM microscope employed (see Section V in the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…32,34,35 Attaining a direct quantitative analysis of atomic-scale charge density variations would require probe sizes well below one angstrom, but this requirement currently exceeds the limits of current technology. 35 An alternative approach involves integrating experimental results with multislice image simulations based on ab initio calculations. Nevertheless, to prevent misinterpretations, it has been recommended that the probe size and shape should be known with very high accuracy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, recent work based on 4D-STEM with center of mass (CoM) images and annular dark field (ADF) have been used to extract the projected electron charge density in monolayer MoS 2 . 28 Similarly, Wen et al , reported on the atomic scale structure and fluctuations of electric fields around edge atoms with different bonding states than bulk atoms in MoS 2 . 29 …”
Section: Metrology For 2d Materialsmentioning
confidence: 89%
“…COM analysis, for example, can be used to obtain electric field and charge distribution maps. 123 This is particularly useful for investigating catalyst–support interactions, in cases where charge transfer between the two is significant. The structure and chemical composition of the catalyst/support system are frequently shown to govern the electronic structure and the resulting activity and stability of the material.…”
Section: Deep Insights Into Pt-based Nanostructures – Advanced (S)tem...mentioning
confidence: 99%